THE CONTRIBUTING FACTORS TO STUDENTS’ DEMOTIVATION IN ENGLISH SPEAKING CLASSES - Sandre, Adhitya Saifulloh; Syahputra, Bayu Kurniawan; Ginting, Kiki Octaviani; Fhadila, Kenny Dwi; Salsabila, Salsabila; Niwanda, Tantri; Amilya, Amilya; Rahmawati, Alivia; Rosdiana, Rosdiana; Sari, Desri Afarmada (JURNAL DIMENSI, 2025)
Speaking is one of the fundamental yet difficult skills for English as a Foreign Language (EFL) learners to master. This study investigates the most significant sources of demotivation among English speaking class students using a mixed-method approach through the distribution of Likert-scale questionnaires and semi-structured interviews to 35 first-year students of an Indonesian English Education Study Program. The findings reveal four general areas of demotivating factors: psychological-emotional, pedagogical-instructional, social-classroom environment, and institutional-technological. Psychological barriers such as fear of mistake, lack of confidence, and fear of peer judgment were revealed as the most salient. Pedagogical issues, particularly a lack of clear evaluation criteria and constructive feedback, also emerged as major contributory factors. Socially, while the majority of students liked group class activities, fear of criticism from peers still influenced their willingness to speak. Technical problems in online learning—i.e., unstable internet, no access to digital devices, and lack of familiarity with virtual communication—also demotivated students' speaking. The study concludes that speaking demotivation is multifaceted in nature and requires holistic solutions addressing both internal learner factors and external learning environments. Recommendations are given to instructors and institutions on how to develop more positive, engaging, and confidence-building speaking classes, both face-to-face and online. Keywords: Anxiety, Demotivation, English Speaking, EFL Learners, Online Learning